Pengaruh Persepsi Manfaat, Kemudahan, Risiko, Dan Pengaruh Sosial Terhadap Keputusan Penggunaan Qris - Maria Augustin Lopes Amaral; Olyva Renyarosari Luan; Apryanus Fallo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the influence of perceived benefits, perceived ease of use, perceived risk, and social influence on the adoption of Quick Response Code Indonesian Standard (QRIS) in Kelapa Lima, Kupang City. The research employed an explanatory quantitative approach involving 144 QRIS users selected through accidental sampling. Data were collected via online questionnaires and analyzed using descriptive statistics, instrument testing, classical assumption testing, and multiple linear regression. The results indicate that perceived benefits, perceived ease of use, perceived risk, and social influence significantly and positively affect QRIS adoption. Among these factors, social influence emerged as the most dominant predictor, while the model accounted for 64.7% of the variation in adoption decisions. The findings suggest that the decision to use QRIS is shaped not only by technical advantages and convenience but also by users’ sense of security and social support.